BIOLOGICAL PROCESSES OF SKIN REGENERATION AFTER PERMANENT MAKEUP: HEALING PHASES - Сабуркіна, Олександра (SWorldJournal, 2025)
The article is devoted to the analysis of biological processes of skin regeneration after permanent makeup with an emphasis on the healing phases. The purpose of the study is to investigate the biological processes of skin regeneration after permanent mak